2019
DOI: 10.33552/ijnc.2019.01.000513
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Topical Application of Mother Breast Milk Versus Distilled Water and Alcohol on Separation Time of Umbilical Cord Stump Among Neonates

Abstract: Umbilical cord infections donate to the increased morbidity and mortality in neonates of developing countries, where neonates are exposed to unhygienic practices. The aim of the study was to monitor the effect of topical application of breast milk compared to distilled water and alcohol on separation time of umbilical cord stump among neonates.Methods: This research was a randomized clinical trial done on 90 mature neonates that were placed randomly in the three groups of study. The umbilical cord separation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 28 publications
0
8
0
2
Order By: Relevance
“…Location of human milk application. 12,13,[15][16][17][21][22][23][24][25]29,[31][32][33][34][35][36] Brodbeck et al It should be noted that even applying HM 1×/d was found to be effective; therefore, mothers should be educated that "applying human milk even once is more effective than not at all." It should also be noted that although applying HM topically with every breastfeed was found to have mixed results, mothers should also be educated that no physical harm will come to the infant if HM is applied more than necessary.…”
Section: Figurementioning
confidence: 99%
See 4 more Smart Citations
“…Location of human milk application. 12,13,[15][16][17][21][22][23][24][25]29,[31][32][33][34][35][36] Brodbeck et al It should be noted that even applying HM 1×/d was found to be effective; therefore, mothers should be educated that "applying human milk even once is more effective than not at all." It should also be noted that although applying HM topically with every breastfeed was found to have mixed results, mothers should also be educated that no physical harm will come to the infant if HM is applied more than necessary.…”
Section: Figurementioning
confidence: 99%
“…All of the articles that defined the dosage of HM topical treatment as "4 to 6 drops" were significant. [22][23][24]…”
Section: Amount Of Applicationmentioning
confidence: 99%
See 3 more Smart Citations